Split Jacobsthal and Jacobsthal-Lucas Quaternions - Yağmur, Tülay (Communications in Mathematics and Applications, 2019)
In this paper, we introduce split Jacobsthal and split Jacobsthal-Lucas quaternions. We obtain generating functions and Binet's formulas for these quaternions. We also investigate some properties of them.
Keywords: Jacobsthal numbers; Jacobsthal-Lucas numbers; Split quaternions; Recurrence relations